Correction: Control of selectivity in allylic alcohol oxidation on gold surfaces: the role of oxygen adatoms and hydroxyl species. Issue 14 (4th March 2015) - Mullen, Gregory M.; Zhang, Liang; Evans, Edward J.; Yan, Ting; Henkelman, Graeme; Mullins, C. Buddie
Abstract : Correction for 'Control of selectivity in allylic alcohol oxidation on gold surfaces: the role of oxygen adatoms and hydroxyl species' by Gregory M. Mullen et al., Phys. Chem. Chem. Phys., 2015, 17, 4730–4738.